Structure-Activity Relationship Studies of β-Lactam-azide Analogues as Orally Active Antitumor Agents Targeting the Tubulin Colchicine Site. Issue 1 (December 2017) - Fu, Dong-Jun; Fu, Ling; Liu, Ying-Chao; Wang, Jun-Wei; Wang, Yu-Qing; Han, Bing-Kai; Li, Xiao-Rui; Zhang, Chuang; Li, Feng; Song, Jian; Zhao, Bing; Mao, Ruo-Wang; et al.
Abstract We have synthesized a series of newβ -lactam-azide derivatives as orally active anti-tumor agents by targeting tubulin colchicine binding site and examined their structure activity relationship (SAR). Among them, compound28 exhibited the most potent antiproliferative activity against MGC-803 cells with an IC50 value of 0.106 μM by induction of G2/M arrest and apoptosis and inhibition of the epithelial to mesenchymal transition.28 acted as a novel inhibitor of tubulin polymerization by its binding to the colchicine site. SAR analysis revealed that a hydrogen atom at the C-3 position of theβ -lactam was required for the potent antiproliferative activity ofβ -lactam-azide derivatives. Oral administration of compound28 also effectively inhibited MGC-803 xenograft tumor growthin vivo in nude mice without causing significant loss of body weight. These results suggested that compound28 is a promising orally active anticancer agent with potential for development of further clinical applications.